Investigation of the dilatant behavior of cracks in the shear response of steel fiber reinforced concrete beams. (1st December 2017) - Gali, Sahith; Subramaniam, Kolluru V.L.
Highlights: Steel fiber reinforced concrete beams with a/d ratio 1.8 tested. A full depth shear crack formed before peak load. Dilatant behavior is identical in beams with and without steel fiber reinforcement. Shear failure is due to loss of aggregate interlock. At 0.75% fiber volume fraction, the crack opening due to dilatancy is arrested. At high fiber volume, failure mode changed from shear to flexure. Abstract: Steel fiber reinforced concrete beams with fiber volume fractions equal to 0.5% and 0.75% are tested with a shear span to depth ratio equal to 1.8. The cracking in the beams is evaluated using the full-field surface displacements obtained from the digital image correlation (DIC) technique. Analysis of images shows that a full depth shear crack is established before the peak load. The displacements measured from across the shear crack indicate a continuous increase in the crack opening displacement associated with increasing slip between the two crack faces. From crack opening and sliding measurements across the shear crack, the dilatant behavior is identical in beams with and without steel fiber reinforcement. Failure in control beams is brittle and results in a large opening of the shear crack. In the SFRC beams with 0.5% volume fraction, there is a continuous decrease in the residual load carrying capacity after the peak load which is associated with an increase in the crack opening displacement. In SFRC beams with 0.75% fiber volume fraction, the increased resistance to crack opening provided by the fibers results in a significantly smaller crack opening and a large increase in the peak load. The crack opening due to dilatancy is arrested, resulting in shear failure by the formation of a secondary shear crack or by flexural failure. The crack opening displacement across the shear crack at the peak load in the load response of the control and the SFRC beams are nominally identical. Failure in shear occurs when the crack opening control provided by the flexural reinforcement and steel fibers is inadequate to sustain the aggregate interlock.